Hubungan Pengetahuan tentang Swamedikasi dengan Pola Penggunaan Obat di Apotek Kimia Farma Senen Jakarta Pusat - Zaenab Durotul Aliyah (Syntax Corporation Indonesia, 2021)
Self-medication is the use of medicine that is done alone without a doctor's prescription. The Central Statistics Agency noted that in 2017 there were 69.43% of the Indonesian population who did self-medication compared to the population who received outpatient treatment at 46.32%. This shows that the behavior of self-medication in Indonesia is still quite large. The purpose of this study was to determine the relationship between knowledge about self-medication and patterns of drug use. This type of research is correlational with a cross sectional approach. The sample in this study were 345 respondents with accidental sampling technique. Data retrieval using questionnaires and statistical analysis using the Spearman Rank correlation test. The results of descriptive analysis of variables in general knowledge about self-medication is good, descriptive analysis of drug use patterns is good. The results showed that there was a significant relationship between knowledge about self-medication and patterns of drug use (p-value 0.001). In conclusion, there is a relationship between knowledge about self-medication and patterns of drug use.